COVID-19: Update on Health Care Workers' Mental Health and Coping During the Pandemic. Issue 1 (January 2022) - Kim, Son Chae; Rankin, Larry
Abstract : During the COVID-19 pandemic, health care workers experienced much higher symptoms of anxiety or depression than during the prepandemic period. As coping mechanisms, high resilience, spirituality, and satisfaction with family functioning were associated with 2- to 3-fold lower odds of anxiety or depression. Health care organizations may consider implementing evidence-based and practical supportive measures to help health care workers maintain good mental health during and after the pandemic.